The Study Examines The Role Of Teachers And Parents In The Ethical Development Of Students At Madrasah Aliyah - Taufiqurrohman Rifa’i; Surahman; Mohamad Ahyar Ma’arif (JIEMAN: Journal of Islamic Educational Management, 2024)
By the mandate of development reform in the context of saving the normalization of national life as the direction of the state, education cannot be separated from educational elements, including educators, parents, students, facilities and infrastructure, society, and educational goals. Starting from the context of the problem that will be solved in this thesis research, the focus is on what problems teachers and parents make in fostering student ethics at MA Sunan Giri Krucil and what form of synergy teachers and parents take in fostering student ethics at MA Sunan Giri Krucil. Researchers used interview, observation, and documentation methods to collect data. They used qualitative descriptive analysis to analyze the data collected in this thesis. In several discussions that have been presented with several analyses and various theories used, the author can draw conclusions related to the Synergy of Teachers and Parents in the Ethical Development of Students at MA Sunan Giri, Krucil Village, Krucil District, Probolinggo Regency, namely the efforts of teachers and parents in fostering student ethics, including students coming to school on time, student study results when completing assignments from the teacher. Then, additional hours are attended by students, assignments given by the teacher are completed, the interaction between parents and teachers, fulfillment of learning tools, and the atmosphere within the family. The obstacles for teachers and parents in developing student ethics at MA Sunan Giri, Krucil Village, Krucil District, Probolinggo Regency, namely that MA students are adults. They are reluctant to be asked to study because social media influence them. Influence by friends, children studying are disturbed by homework and student conditions, and sometimes students are in a stall when entering class. Sesuai dengan amanat reformasi pembangunan dalam rangka penyelamatan normalisasi kehidupan Nasional sebagai haluan negara, dalam pendidikan tidak terlepas dari unsur pendidikan diantaranya pendidik, orang tua, peserta didik, sarana dan prasarana, masyarakat dan tujuan pendidikan. Bertolak dari kontek pemasalahan yang akan di pecahkan dalam penelitian skripsi ini di fokuskan dalam masalah apa saja usaha-usaha guru dan orang tua dalam pembinaan etika siswa di MA Sunan Giri Krucil dan bagaimana bentuk sinergitas guru dan orang tua dalam membina etika siswa di MA Sunan Giri Krucil, Dalam pengumpulan data peneliti menggunakan metode wawancara, observasi dan dokumentasi, dalam menganalisis data yang terkumpul dalam skripsi ini menggunakan analis Diskriptif Kualitatif. Dalam beberapa pembahasan yang telah di paparkan dengan beberapa analisa dan berbagai teori yang di gunakan, maka penulis dapat menarik kesimpulan terkait dengan Sinergitas Guru dan Orang Tua Dalam Pembinaan Etika Siswa DI MA Sunan Giri Desa Krucil Kecamatan Krucil Kabupaten Probolinggo yaitu usaha guru dan orang tua dalam membina etika siswa, diantaranya siswa itu datang ke sekolah tepat waktu, Hasil studi siswa ketika menyelesaikan tugas dari guru. Kemudian adanya jam tambahan yang diikuti oleh siswa, Tugas yang diberikan oleh guru terselesaikan, Interaksi orang tua dengan guru, pemenuhan alat belajar kemudian suasana didalam keluarga. Adapun hambatan-hambatan guru dan orang tua dalam membina etika siswa di MA Sunan Giri Desa Krucil kecamatan krucil Kabupaten Probolinggo yaitu siswa MA itu sudah dewasa dan enggan jika disuruh belajar karena dipengaruhi oleh media sosial. Pengaruh dari teman, Terkadang anak sedang belajar diganggu dengan tugas-tugas rumah, Kondisi siswa, Ketika masuk kelas terkadang siswa ada di warung.